Melancholy and the Otherness of God: A Study in the Genealogy, Hermeneutics, and Therapeutics of Depression - Feld, Alina N. (Lexington Books, 2011)
An impressive study that prompts the reader toward philosophical reflection on the hermeneutics of melancholy in its relation to maturing theological understanding and cultivation of a profound self-consciousness. Melancholy has been interpreted as a deadly sin or demonic temptation to non-being, yet its history of interpretation reveals a progressive coming to terms with the dark mood that ultimately unveils it as the self's own ground and a trace of the abysmal nature of God. The book advances two provocative claims: that far from being a contingent condition, melancholy has been progressively acknowledged as constitutive of subjectivity as such, a trace of divine otherness and pathos, and that the effort to transcend melancholy-like Perseus vanquishing Medusa-is a necessary labor of maturing self-consciousness. Reductive attempts to eliminate it, besides being dangerously utopian, risk overcoming the labor of the soul that makes us human. This study sets forth a rigorous scholarly argument that spans several disciplines, including philosophy, theology, psychology, and literary studies.